Neck biomechanics indicate that giant Transylvanian azhdarchid pterosaurs were short-necked arch predators - Naish, Darren; Witton, Mark P. (PeerJ, 2017)
Azhdarchid pterosaurs include the largest animals to ever take to the skies with some species exceeding 10 metres in wingspan and 220 kg in mass. Associated skeletons show that azhdarchids were long-necked, long-jawed predators that combined a wing planform suited for soaring with limb adaptations indicative of quadrupedal terrestrial foraging. The postcranial proportions of the group have been regarded as uniform overall, irrespective of their overall size, notwithstanding suggestions that minor variation may have been present. Here, we discuss a recently discovered giant azhdarchid neck vertebra referable to Hatzegopteryx from the Maastrichtian Sebeş Formation of the Transylvanian Basin, Romania, which shows how some azhdarchids departed markedly from conventional views on their proportions. This vertebra, which we consider a cervical VII, is 240 mm long as preserved and almost as wide. Among azhdarchid cervicals, it is remarkable for the thickness of its cortex (4–6 mm along its ventral wall) and robust proportions. By comparing its dimensions to other giant azhdarchid cervicals and to the more completely known necks of smaller taxa, we argue that Hatzegopteryx had a proportionally short, stocky neck highly resistant to torsion and compression. This specimen is one of several hinting at greater disparity within Azhdarchidae than previously considered, but is the first to demonstrate such proportional differences within giant taxa. On the assumption that other aspects of Hatzegopteryx functional anatomy were similar to those of other azhdarchids, and with reference to the absence of large terrestrial predators in the Maastrichtian of Transylvania, we suggest that this pterosaur played a dominant predatory role among the unusual palaeofauna of ancient Haţeg.
Keywords: Pterosaurs; Azhdarchids; Cretaceous; Biomechanics; Maastrichtian